Formulation optimization of Docetaxel loaded self-emulsifying drug delivery system to enhance bioavailability and anti-tumor activity - Valicherla, Guru R. (Sci Rep, 2016)
Poor bioavailability of Docetaxel (DCT) arising due to its low aqueous solubility and permeability limits its clinical utility. The aim of the present study was to develop DCT loaded self-emulsified drug delivery systems (D-SEDDS) and evaluate its potential ability to improve the oral bioavailability and therapeutic efficacy of DCT. D-SEDDS were characterized for their in vitro antitumor activity, in situ single pass intestinal perfusion (SPIP), bioavailability, chylomicron flow blocking study and bio-distribution profile. The D-SEDDS were prepared using Capryol 90, Vitamin E TPGS, Gelucire 44/14 and Transcutol HP with a ratio of 32.7/29.4/8.3/29.6 using D-Optimal Mixture Design. The solubility of DCT was improved upto 50 mg/mL. The oral bioavailability of the D-SEDDS in rats (21.84 ± 3.12%) was increased by 3.19 fold than orally administered Taxotere (6.85 ± 1.82%). The enhanced bioavailability was probably due to increase in solubility and permeability. In SPIP, effective permeability of D-SEDDS was significantly higher than Taxotere. D-SEDDS showed 25 fold more in vitro cytotoxic activity compared to free DCT. Chylomicron flow blocking study and tissue distribution demonstrated the intestinal lymphatic transport of D-SEDDS and higher retention in tumor than Taxotere. The data suggests that D-SEDDS showed desired stability, enhanced oral bioavailability and in vitro antitumor efficacy.